Analysis of Contract Change Order (CCO) Factors, which Affect the Fly Over Work (Case Study of The Cisauk Fly Over Development Project) - Sukardi, Indra Mahendra; Biantoro, Agung Wahyudi (ASTONJADRO, 2025)
Every project can be guaranteed to experience change orders, which occur at the request of the contractor or owner. Change orders are governed by the terms of the contract. So the projects carried out are usually carried out with results that are not in accordance with what was planned. This research aims to find out what factors cause Contract Change Orders (CCO), which influence the Cisauk flyover work, Tangerang Regency. This research was conducted by distributing questionnaires and respondents to the Cisauk flyover construction project, Tangerang Regency. The research method uses quantitative analysis and questionnaire data processing using Statistic program with the analysis method of questionnaire validity test, questionnaire reliability test, correlation test, factor analysis test and Relative Important Index (RII). The results of the research obtained a ranking order for each factor and obtained the dominant factors that influence the occurrence of a Contract Change Order (CCO). There are 6 (six) research variables for problem formulation, namely contract documents (X1), planning and design (X2), owner involvement (X3), environmental or external conditions (X4), contractors (X5), and resources (X6), Factors that influence the occurrence of a Contract Change Order (CCO) for the Cisauk flyover work based on ranking order 1 to 5 are X.2.5 mismatch between design drawings and field conditions (RII: 0.814), X.2.1 Errors in planning drawings (RII : 0.745), The most dominant factor influencing the occurrence of a Contract Change Order (CCO) on the Cisauk fly over project is the indicator that comes from variable X2, namely planning and design.